Research Design of the Main Parameters of the Quarry - Tukhtashev Alisher Bahadirovich; Abdurashidov Shakhriyor Mashrabjon ugli (Zien Journals, 2022)
The article deals with the study of the design of the main parameters of a quarry. The correct choice of the depth and contours of the quarry is described, since they determine the volumes of minerals involved in the development.
Keywords: design productivity of a quarry; working site